Stretched acrylic resin film
By controlling the Zn/Xn and Zn/Yn values determined by polarization Raman spectroscopy in the acrylic resin stretched film, optimizing the orientation state of the film, solving the problem of insufficient crack resistance of functional films in the prior art, and realizing the acrylic resin The stretched film has high crack resistance and fracture resistance, and is suitable for frameless liquid crystal display devices.
Patent Information
- Application Number
- CN202380049206.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-28
- Publication Date
- 2025-02-18
AI Technical Summary
In liquid crystal display devices, with the requirement of higher performance, especially frameless demand, crack resistance of the existing functional film is not sufficient, and cracks during cutting are difficult to suppress.
By controlling the Zn/Xn and Zn/Yn values measured by the acrylic resin stretched film within a specific range, the orientation state of the film is optimized to improve its crack resistance and fracture resistance.
The excellent crack resistance and fracture resistance of the acrylic resin stretched film are achieved, making it suitable for use in polarizer protection films for frameless liquid crystal display devices.
Smart Images

Figure CN119487426A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an acrylic resin stretched film, and more particularly, to an acrylic resin stretched film having excellent crack resistance and break resistance. Background Art
[0002] Liquid crystal display devices are often used as display devices for various electronic devices. In recent years, such electronic devices have been increasingly miniaturized, and liquid crystal display devices are also required to be miniaturized and lightweight.
[0003] In such a liquid crystal display device, various functional films such as a polarizer protection film for protecting a polarizer, a diffusion film, and a light-collecting film are used to achieve desired optical characteristics.
[0004] For example, Patent Document 1 proposes a stretched film made of an amorphous thermoplastic resin as a functional film used for optical applications, the stretched film satisfying the following conditions (i) and (ii) at the same time.
[0005] (i) The in-plane orientation degree Dpl in polarized Raman spectroscopy is 0.3 or more and 3.0 or less.
[0006] (ii) The thickness orientation degree Dth in polarized Raman spectroscopy is 0.1 or more and 0.25 or less, or 4 or more and 10 or less.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2010-58455 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] On the other hand, in liquid crystal display devices, with the demand for high performance in recent years, such as the demand for frameless, various functional films constituting liquid crystal display devices are also required to cope with frameless. From the viewpoint of coping with frameless, it is expected that cracks will be suppressed when the functional film is cut into the desired size. In particular, such cracks are mostly generated near the cut portion, so in the case of a liquid crystal display device with a frame, even if cracks are generated near the cut portion, they can be covered by the frame, but in the case of forming a frameless device, such cracks cannot be covered by the frame, so it will become a problem. In contrast, the crack resistance of existing functional films such as the stretched film disclosed in the above-mentioned patent document 1 is not sufficient, so from the above-mentioned viewpoint, it is expected to improve the crack resistance.
[0012] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide an acrylic resin stretched film having excellent crack resistance and break resistance.
[0013] Solutions for solving problems
[0014] The present inventors conducted intensive research to achieve the above-mentioned purpose and found that an acrylic resin stretched film in which Zn / Xn and Zn / Yn are controlled within a specific range as determined by polarized Raman spectroscopy can achieve excellent crack resistance and fracture resistance, thereby completing the present invention.
[0015] [1] An acrylic resin stretched film formed by molding an acrylic resin, wherein Zn / Xn and Zn / Yn of the acrylic resin stretched film obtained by polarization Raman spectroscopy satisfy the following formula (1) and the following formula (2).
[0016] Zn / Xn≤1.00···(1)
[0017] Zn / Yn≤1.00···(2)
[0018] (Xn is Xn=Xd 970-1010 / Xs 2930-2970 The calculated value,
[0019] Yn is given by Yn=Yd 970-1010 / Ys 2930-2970 The calculated value,
[0020] Zn is Zn=Zd 970-1010 / Zs 2930-2970 The calculated value,
[0021] XD 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy measurement parallel to the winding direction (MD direction) of the acrylic resin stretched film (X direction). -1 The minimum value of the second differential peak of the peak within the range,
[0022] Xs 2930-2970 The wave number is 2930 to 2970 cm-1 obtained by polarization Raman spectroscopy measurement parallel to the winding direction (MD direction) of the acrylic resin stretched film (X direction). -1 The minimum value of the second differential peak of the peak within the range,
[0023] Y 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy measurement perpendicular to the winding direction (MD direction) of the acrylic resin stretched film (Y direction). -1The minimum value of the second differential peak of the peak within the range,
[0024] Ys 2930-2970 The wave number is 2930 to 2970 cm-1 obtained by polarized Raman spectroscopy measurement perpendicular to the winding direction (MD direction) of the acrylic resin stretched film (Y direction). -1 The minimum value of the second differential peak of the peak within the range,
[0025] Zd 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy along the thickness direction (Z direction) of the acrylic resin stretched film. -1 The minimum value of the second differential peak of the peak within the range,
[0026] Z 2930-2970 The wave number is 2930-2970cm obtained by polarized Raman spectroscopy along the thickness direction (Z direction) of the acrylic resin stretched film. -1 The minimum value of the second derivative peak of the peak within the range. )
[0027] [2] The acrylic resin stretched film according to [1], wherein the in-plane retardation R0 of the stretched film with respect to light of a wavelength of 589 nm is 10 nm or less.
[0028] [3] The acrylic resin stretched film according to any one of [1] to [2], wherein the thickness direction retardation Rth with respect to light of a wavelength of 589 nm is -10 to +10 nm.
[0029] [4] The acrylic resin stretched film according to any one of [1] to [3], wherein the glass transition temperature (Tg) is 100° C. or higher and 200° C. or lower.
[0030] [5] The acrylic resin stretched film according to any one of [1] to [4], wherein the acrylic resin contains a (meth)acrylic polymer having a ring structure.
[0031] [6] The acrylic resin stretched film according to [5], wherein the acrylic resin contains a (meth)acrylic polymer having a ring structure in its main chain.
[0032] [7] The acrylic resin stretched film according to [5] or [6], wherein the ring structure is at least one selected from the group consisting of a lactone ring structure, a glutarimide structure, a glutaric anhydride structure, an N-substituted maleimide structure, and a maleic anhydride structure.
[0033] [8] The acrylic resin stretched film according to any one of [5] to [7], wherein the ring structure is a lactone ring structure.
[0034] [9] The acrylic resin stretched film according to any one of [1] to [8], wherein the acrylic resin contains a UV absorber.
[0035]
[10] The acrylic resin stretched film according to any one of [1] to [9], wherein the film thickness is 35 to 45 μm.
[0036]
[11] A polarizer protective film comprising the stretched acrylic resin film according to any one of [1] to
[10] .
[0037]
[12] A method for producing a stretched acrylic resin film, which is a method for producing a stretched acrylic resin film according to any one of [1] to
[10] , the method comprising a stretching step of stretching a film of an acrylic resin.
[0038] The stretching temperature in the stretching step is glass transition point Tg+25°C to 29°C, and the stretching strain rate is 90 to 600% / min.
[0039] Effects of the Invention
[0040] According to the present invention, there can be provided an acrylic resin stretched film having excellent crack resistance and break resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a diagram showing an example of a method for producing an acrylic resin stretched film according to one embodiment of the present invention.
[0042] Figure 2A A diagram showing the measurement direction of polarized Raman spectroscopy.
[0043] Figure 2B This is a graph showing a curve obtained by polarization Raman spectroscopy measurement in the X direction of the acrylic resin stretched film of Example 1.
[0044] Figure 2C 3 is a graph showing a second derivative curve of the polarized Raman spectrum in the X direction of the stretched acrylic resin film of Example 1. DETAILED DESCRIPTION
[0045] <Acrylic resin stretched film>
[0046] The acrylic resin stretched film of the present invention is an acrylic resin stretched film formed by molding an acrylic resin, wherein Zn / Xn and Zn / Yn of the acrylic resin stretched film obtained by polarization Raman spectroscopy satisfy the following formula (1) and the following formula (2).
[0047] Zn / Xn≤1.00···(1)
[0048] Zn / Yn≤1.00···(2)
[0049] The acrylic resin stretched film of the present invention is a film formed by molding an acrylic resin, and therefore contains an acrylic resin. In addition, the acrylic resin used in the present invention is a resin containing a (meth)acrylic polymer.
[0050] The (meth)acrylic polymer contained in the acrylic resin used in the present invention is a polymer having a structural unit derived from a (meth)acrylic acid ester monomer, that is, a (meth)acrylic acid ester monomer unit. The content of the (meth)acrylic acid ester monomer unit in the (meth)acrylic acid polymer is usually 10% by mass or more, preferably 30% by mass or more, more preferably 50% by mass or more, and particularly preferably 70% by mass or more.
[0051] Examples of the (meth)acrylate constituting the (meth)acrylate monomer unit include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, allyloxyhexyl (meth)acrylate, and 2,3,4,5-tetrahydroxypentyl (meth)acrylate.
[0052] The (meth)acrylic polymer preferably has a methyl (meth)acrylate monomer unit. By containing the methyl (meth)acrylate monomer unit, the optical properties and thermal stability of the acrylic resin stretched film can be further improved. The (meth)acrylic polymer may have two or more (meth)acrylate monomer units.
[0053] The (meth)acrylic polymer may also contain units of copolymerizable monomers other than the (meth)acrylate units. Examples of such copolymerizable monomers include styrene, vinyltoluene, α-methylstyrene, α-hydroxymethylstyrene, α-hydroxyethylstyrene, acrylonitrile, methacrylonitrile, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinylpyrrolidone, and N-vinylcarbazole. The (meth)acrylic polymer may contain units of two or more copolymerizable monomers.
[0054] In addition, the (meth)acrylic polymer may have a ring structure, and when it has a ring structure, it is preferred that the main chain has a ring structure. The ring structure can make the heat resistance and optical properties more excellent. For example, the ring structure can be introduced into the main chain of the (meth)acrylic polymer by a method of copolymerizing a (meth)acrylic ester monomer and a monomer having a ring structure, or by a method of polymerizing a monomer group containing a (meth)acrylic ester monomer and then performing a cyclization reaction.
[0055] In the case of introducing a ring structure in the main chain by a cyclization reaction after polymerization, the (meth) acrylic polymer is preferably formed by copolymerization with a monomer having a hydroxyl group and / or a carboxylic acid group. As a monomer having a hydroxyl group, for example, 2-(hydroxymethyl) methyl acrylate, 2-(hydroxymethyl) ethyl acrylate, 2-(hydroxymethyl) isopropyl acrylate, 2-(hydroxymethyl) butyl acrylate, 2-(hydroxyethyl) methyl acrylate, methallyl alcohol, allyl alcohol, etc. can be cited. As a monomer having a carboxylic acid group, for example, acrylic acid, methacrylic acid, crotonic acid, 2-(hydroxymethyl) acrylic acid, 2-(hydroxyethyl) acrylic acid, etc. can be cited. These monomers can use more than two kinds.
[0056] When the (meth)acrylic polymer has a ring structure in the main chain, the ring structure is preferably at least one selected from the group consisting of a lactone ring structure, a glutarimide structure, a glutaric anhydride structure, an N-substituted maleimide structure, and a maleic anhydride structure. From the viewpoint of further improving the optical properties, a lactone ring structure and a glutarimide structure are preferred, and a lactone ring structure is more preferred.
[0057] Examples of the lactone structure include the structure disclosed in Japanese Unexamined Patent Publication No. 2004-168882, and the structure represented by the following general formula (1) is preferred from the viewpoint of further improving the optical properties.
[0058]
[0059] In the above general formula (1), R 1 , R 2 and R 3 Each is independently a hydrogen atom or an organic group having 1 to 20 carbon atoms.
[0060] Examples of the organic group in the general formula (1) include alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, and propyl groups, unsaturated aliphatic hydrocarbon groups having 2 to 20 carbon atoms, such as vinyl and propenyl groups, and aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as phenyl and naphthyl groups. One or more hydrogen atoms of these alkyl groups, unsaturated aliphatic hydrocarbon groups, and aromatic hydrocarbon groups may be substituted by at least one group selected from the group consisting of a hydroxyl group, a carboxyl group, an ether group, and an ester group.
[0061] The glutarimide structure is not particularly limited, but is preferably a structure represented by the following general formula (2) from the viewpoint of further improving optical properties.
[0062]
[0063] In the above general formula (2), R 4 , R 5 are independently a hydrogen atom or a methyl group, R 6 It is a hydrogen atom, a linear alkyl group having 1 to 6 carbon atoms, a cyclopentyl group, a cyclohexyl group, a benzyl group or a phenyl group.
[0064] When the (meth)acrylic polymer has a ring structure in the main chain, the content of the monomer unit forming the ring structure is preferably 1 to 80% by weight, more preferably 5 to 70% by weight, and further preferably 10 to 60% by weight.
[0065] Examples of the (meth)acrylic polymer having a lactone ring structure in the main chain include polymers described in JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084, and the like can be synthesized by the methods described in these publications. In addition, examples of (meth)acrylic polymers having a glutarimide structure in the main chain include polymers described in JP-A-2006-309033, JP-A-2006-317560, JP-A-2006-328329, JP-A-2006-328334, JP-A-2006-337491, JP-A-2006-337492, JP-A-2006-337493, JP-A-2006-337569, and JP-A-2007-009182, and the like can be cited, and can be synthesized by the methods described in these gazettes.
[0066] The weight average molecular weight of the (meth)acrylic polymer is preferably 10,000 to 500,000, more preferably 20,000 to 400,000, and further preferably 30,000 to 300,000. The weight average molecular weight of the (meth)acrylic polymer can be determined by GPC as a value converted to polystyrene.
[0067] The acrylic resin used in the present invention preferably contains the above-mentioned (meth)acrylic polymer, and its glass transition temperature Tg is preferably 100°C to 200°C, more preferably 110°C to 160°C, further preferably 120°C to 130°C, and most preferably 125°C to 130°C.
[0068] Furthermore, the acrylic resin stretched film of the present invention is an acrylic resin stretched film obtained by molding the above-mentioned acrylic resin, and the acrylic resin stretched film is measured by polarization Raman spectroscopy.
[0069] Zn / Xn and Zn / Yn satisfy the following formula (1) and the following formula (2).
[0070] Zn / Xn≤1.00···(1)
[0071] Zn / Yn≤1.00···(2)
[0072] Here, the above Xn is given by Xn=Xd 970-1010 / Xs 2930-2970 The calculated value,
[0073] Yn is given by Yn=Yd 970-1010 / Ys 2930-2970 The calculated value,
[0074] Zn is Zn=Zd 970-1010 / Zs 2930-2970 Calculated value.
[0075] In addition, Xd 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy measurement parallel to the winding direction (MD direction) of the acrylic resin stretched film (X direction). -1 The minimum value of the second differential peak of the peak within the range,
[0076] Xs 2930-2970 The wave number is 2930 to 2970 cm-1 obtained by polarization Raman spectroscopy measurement parallel to the winding direction (MD direction) of the acrylic resin stretched film (X direction). -1 The minimum value of the second differential peak of the peak within the range,
[0077] Y 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy measurement perpendicular to the winding direction (MD direction) of the acrylic resin stretched film (Y direction). -1 The minimum value of the second differential peak of the peak within the range,
[0078] Ys 2930-2970 The wave number is 2930 to 2970 cm-1 obtained by polarized Raman spectroscopy measurement perpendicular to the winding direction (MD direction) of the acrylic resin stretched film (Y direction). -1 The minimum value of the second differential peak of the peak within the range,
[0079] Zd 970-1010The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy along the thickness direction (Z direction) of the acrylic resin stretched film. -1 The minimum value of the second differential peak of the peak within the range,
[0080] Z 2930-2970 The wave number is 2930-2970cm obtained by polarized Raman spectroscopy along the thickness direction (Z direction) of the acrylic resin stretched film. -1 The minimum value of the second differential peak of the peak within the range.
[0081] In order to improve the crack resistance and fracture resistance of acrylic resin stretched films, the inventors of the present invention have conducted in-depth research on the relationship between the orientation state in the winding direction (X direction) of the acrylic resin stretched film, the orientation state in the direction (Y direction) perpendicular to the winding direction (X direction) of the acrylic resin stretched film, and the orientation state in the thickness direction (Z direction) of the acrylic resin stretched film. As a result, it was found that for the winding direction (X direction), the direction perpendicular to it (Y direction), and the thickness direction (Z direction), focusing on the wave number 970 to 1010 cm obtained by polarized Raman spectroscopy measurement, -1 The peaks in the range of 2930-2970 cm -1 The present invention has been completed by controlling Xn, Yn and Zn obtained by the minimum values of these secondary differential peaks within a specific range, thereby achieving excellent crack resistance and fracture resistance. In particular, the present inventors conducted research and found that in stretched films such as acrylic resin stretched films, when either crack resistance or fracture resistance is improved, the other tends to decrease, and it is difficult to improve these crack resistance and fracture resistance at the same time. As a result, it was found that by controlling Xn, Yn and Zn within a specific range, excellent crack resistance and fracture resistance can be achieved.
[0082] More specifically, the peaks with higher orientation dependence are focused on the wave numbers 970 to 1010 cm -1 The peak in the range of 2930 to 2970 cm-1 and the minimum value of the secondary differential peak are also considered. -1 In the present invention, Xn, Yn and Zn calculated using these are controlled to be within a specific range. More specifically, the ratio of Zn to Xn, i.e., the Raman intensity ratio (Zn / Xn), and the ratio of Zn to Yn, i.e., the Raman intensity ratio (Zn / Yn), are controlled to be within a specific range.
[0083] Furthermore, the essence of this study is that the orientation state of the stretched film plane (XY plane) is optimized based on the conventional orientation control of stretching, while in contrast, in the present invention, orientation is given very weakly in the thickness direction, thereby suppressing cracks during cutting and greatly improving crack resistance.
[0084] When the acrylic resin stretched film does not satisfy any of the above formula (1) and the above formula (2), the crack resistance may be deteriorated depending on the cutting direction.
[0085] It should be noted that Xn, Yn, and Zn can be obtained by performing polarization Raman spectroscopy on the acrylic resin stretched film. Specifically, polarization Raman spectroscopy is performed parallel (X direction) to the winding direction (MD direction) of the acrylic resin stretched film, and polarization Raman spectroscopy is performed perpendicular (Y direction) to the winding direction (MD direction) of the acrylic resin stretched film, and polarization Raman spectroscopy is performed along the thickness direction (Z direction) of the acrylic resin stretched film, so that Xn, Yn, and Zn can be obtained. It should be noted that polarization Raman spectroscopy can be performed, for example, as follows: a laser Raman spectrometer (product name "NRS-5500", manufactured by JASCO Corporation) is used as a measuring device to perform polarization Raman spectroscopy, and the wave number in each measuring direction is 970 to 1010 cm -1 Peaks in the range of 2930 to 2970 cm -1 Calculate the peaks in the range of wave numbers, calculate their secondary differential peaks, and find the minimum value of the secondary differential peaks in these wave number ranges. According to Xn = Xd 970-1010 / Xs 2930-2970 、Yn=Yd 970-1010 / Ys 2930-2970 、Zn=Zd 970-1010 / Zs 2930-2970 It should be noted that the calculation of the second derivative peak may be performed using calculation software or the like provided in the laser Raman spectrometer.
[0086] Figure 2B , Figure 2C , a curve obtained by polarized Raman spectroscopy measurement of the acrylic resin stretched film of Example 1 is shown. Here, Figure 2A : is a diagram showing the measurement direction of polarized Raman spectroscopy. Figure 2B : is a graph showing a curve obtained by polarized Raman spectroscopy measurement in the X direction of the acrylic resin stretched film of Example 1. Figure 2C 3 is a graph showing a second derivative curve of the polarized Raman spectrum in the X direction of the stretched acrylic resin film of Example 1.
[0087] The winding direction (MD direction: Machine Direction) of the stretched acrylic resin film is the running direction (flow direction) of the film when the stretched acrylic resin film is formed by stretching an unstretched acrylic resin film.
[0088] In addition, Zn / Xn and Zn / Yn of the acrylic resin stretched film of the present invention only need to satisfy the above-mentioned formula (1) and the above-mentioned formula (2), and the number of folding endurance (MIT number) based on the folding endurance test conducted in the winding direction (MD direction) and the direction perpendicular to the winding direction (TD direction: Transverse Direction) of the acrylic resin stretched film preferably satisfies the following formula (3) and the following formula (4).
[0089] 0.74≤MIT number in TD direction / MIT number in MD direction≤1.35···(3)
[0090] 40≤(MIT times in MD direction + MIT times in TD direction) / 2≤197···(4)
[0091] The folding endurance test (MIT test) can be performed according to JIS P8115. Preferably, the folding endurance number (MIT number) measured according to JIS P8115 satisfies the above formula (3) and the above formula (4). By satisfying the above formula (3) and the above formula (4), the folding endurance number (MIT number) can effectively suppress the film from breaking while making the crack resistance more excellent. It should be noted that it is more preferable that the folding endurance number (MIT number) satisfies the following formula (5) and the following formula (6).
[0092] 0.95≤MIT number in TD direction / MIT number in MD direction≤1.32···(5)
[0093] 45≤(MIT times in MD direction + MIT times in TD direction) / 2≤166···(6)
[0094] In addition, the impact strength of the acrylic resin stretched film of the present invention is preferably in the range of 1.90 to 2.15 kJ / m, and more preferably in the range of 1.94 to 2.12 kJ / m. By making the impact strength in the above range, the film can be effectively prevented from breaking and the crack resistance can be made more excellent. The impact strength (kJ / m) can be obtained by measuring the impact value (kJ) when a hammer with a hammer capacity of 1.5 J and a hammer tip diameter of 1 inch hits the acrylic resin stretched film.
[0095] The in-plane phase difference R0 of the acrylic resin stretched film of the present invention for light with a wavelength of 589 nm is preferably 10 nm or less, more preferably 0 to 5 nm, and further preferably 0 to 3 nm. In addition, the thickness direction phase difference Rth of the acrylic resin stretched film of the present invention for light with a wavelength of 589 nm is preferably -10 to +10 nm, more preferably -5 to +5 nm, and further preferably -3 to +3 nm. By making the in-plane phase difference R0 and the thickness direction phase difference Rth within the above range, the optical properties as a polarizer protective film can be excellent. The in-plane phase difference R0 and the thickness direction phase difference Rth can be obtained by a phase difference measuring device.
[0096] The glass transition temperature Tg of the acrylic resin stretched film of the present invention is preferably 100°C to 200°C, more preferably 110°C to 160°C, further preferably 120°C to 130°C, and most preferably 125°C to 130°C.
[0097] The thickness (film thickness) of the acrylic resin stretched film of the present invention is not particularly limited and may be appropriately selected depending on the intended use, but is 35 to 45 μm, preferably 37 to 43 μm, and more preferably 39 to 41 μm.
[0098] <Method for producing acrylic resin stretched film>
[0099] The method for producing the acrylic resin stretched film of the present invention is not particularly limited, but the production method of the present invention described below is preferred from the viewpoint that Zn / Xn and Zn / Yn obtained by polarization Raman spectroscopy can be appropriately controlled within the above ranges.
[0100] That is, the manufacturing method of the present invention comprises the following steps:
[0101] A preheating step, which preheats the unstretched acrylic resin film;
[0102] The stretching step is to heat the unstretched acrylic resin film to a stretching temperature T E [℃] in one direction or two directions; and
[0103] The thermal relaxation step is to heat the stretched acrylic resin film at a relaxation temperature T R [℃] for heat relaxation,
[0104] Due to the relationship with the glass transition temperature Tg [°C] of the acrylic resin, the stretching temperature T E [℃] controlled as T E =The range of Tg+25 to Tg+29.
[0105] Figure 1FIG. 1 is a diagram showing an example of a method for producing an acrylic resin stretched film according to an embodiment of the present invention. Figure 1 The case where an acrylic resin stretched film is produced by the method shown is described.
[0106] Figure 1 This is a diagram showing a method of simultaneously stretching an acrylic resin film in the longitudinal direction and the width direction using a simultaneous biaxial stretching apparatus equipped with a preheating zone, a stretching zone, and a heat relaxation zone. Figure 1 In the example shown, the unstretched acrylic resin film is preheated in a preheating zone using a simultaneous biaxial stretching device, stretched simultaneously in the length direction and the width direction while being heated in a stretching zone, and a heat relaxation treatment is performed in a heat relaxation zone to uniformize the molecular orientation (orientation angle) of the film. It should be noted that the stretching method is not limited to the method using Figure 1 The simultaneous biaxial stretching in the simultaneous biaxial stretching apparatus shown above may be, for example, sequential stretching. In the case of sequential stretching, for example, a tenter stretching machine including a preheating zone, a stretching zone, and a heat relaxation zone may be used.
[0107] The stretching process is Figure 1 The film 100 is preheated in the preheating zone shown in the figure, and the preheated film 100 is heated and stretched in the longitudinal direction and the width direction in the stretching zone. Specifically, in the stretching process, the film 100 is first continuously fed from a roller or the like, and the film 100 is clamped at regular intervals using a plurality of clamps 200, and each clamp 200 is moved to transport the film 100 to a simultaneous biaxial stretching device. Next, the film 100 is transported while being stretched in a Figure 1 After preheating in the preheating zone shown, the film 100 is heated to the stretching temperature T in the stretching zone. E [°C], the sheet is pulled in the longitudinal direction and the width direction by the clamp 200 to be stretched.
[0108] It should be noted that in this embodiment, a pair of guide rails (not shown) are provided for moving the clamp 200 so as to pass through the simultaneous biaxial stretching device. Figure 1 The position of the clamp 200 on the upper side of the film 100 shown and the position of the clamp 200 clamping the lower side are parallel to each other in the preheating zone, are separated from each other in the width direction of the film 100 in the stretching zone, and are parallel to each other in the heat relaxation zone. Alternatively, in the heat relaxation zone, the distance between the pair of guide rails can be made close in the width direction in consideration of the shrinkage amount when the film is cured. In this embodiment, the clamp 200 clamping the film 100 moves along such a guide rail, thereby enabling the film 100 to be conveyed and stretched.
[0109] The film 100 can be obtained, for example, by melt-extruding a thermoplastic resin through a T-die.
[0110] In the manufacturing method of the present invention, the stretching temperature T in the stretching step is set to 0.1°C due to the relationship with the glass transition temperature Tg [°C] of the acrylic resin constituting the film 100. E [℃] Extremely limited to T E =Tg+25 to Tg+29, thereby Zn / Xn and Zn / Yn can be appropriately controlled to the above range. That is, when the glass transition temperature Tg[°C] of the acrylic resin is, for example, 125°C, the stretching temperature T in the stretching step is E [°C] is extremely limited to the range of 150 to 154°C. In the present invention, the glass transition temperature Tg [°C] of the acrylic resin refers to a temperature (glass transition temperature specified by the midpoint method) that is a midpoint of the displacement of the endothermic curve observed by differential scanning calorimetry (DSC) (a temperature between the start temperature of the displacement and the end temperature of the displacement, a midpoint glass transition temperature).
[0111] Stretching temperature T E [°C] When the glass transition temperature Tg [°C] relative to the acrylic resin is lower than (Tg+25) [°C], the values of the above formula (1) and the above formula (2) become excessively large, and the above formula (1) and the above formula (2) are not satisfied. On the other hand, when it exceeds (Tg+29) [°C], it is assumed that the above formula (1) and the above formula (2) are satisfied, but the fracture resistance is significantly reduced and production becomes impossible. Therefore, Zn / Xn and Zn / Yn are preferably 0.70 or more, and more preferably 0.93 or more.
[0112] It should be noted that the stretching temperature T E [°C] The glass transition temperature Tg [°C] of the acrylic resin may be in the above range, and is preferably set to Tg [°C] in relation to the extrapolated glass transition start temperature Tig [°C] of the acrylic resin. E =Tig+27~Tg+31. The glass transition temperature Tg (midpoint glass transition temperature) and the extrapolated glass transition start temperature Tig of the acrylic resin can be obtained, for example, by using a differential scanning calorimeter (product name "DSC8500", manufactured by PerkinElmer Co., Ltd.) as a differential scanning calorimetry (DSC) device, measuring at a heating rate of 10°C / min, and using the analysis software attached to the device based on the obtained DSC curve.
[0113] The stretching ratio in the stretching process is not particularly limited, and the longitudinal stretching ratio (stretching ratio in the MD direction) is preferably 1.5 to 3.0 times, more preferably 2.0 to 2.5 times, and the transverse stretching ratio (stretching ratio in the TD direction) is preferably 1.5 to 3.0 times, more preferably 2.0 to 2.5 times. If the stretching ratio is too low, the optical properties of the obtained acrylic resin stretched film may become insufficient. In addition, if the stretching ratio is too high, it may become difficult to control the values of Zn / Xn and Zn / Yn to the above range.
[0114] In addition, the stretching strain rate in the stretching process is not particularly limited, and the longitudinal stretching strain rate (stretching strain rate in the MD direction) is preferably 90 to 600% / min, more preferably 150 to 250% / min, and the transverse stretching strain rate (stretching strain rate in the TD direction) is preferably 90 to 600% / min, more preferably 150 to 250% / min. Even if the stretching strain rate is too small or too large, it sometimes becomes difficult to control the values of Zn / Xn and Zn / Yn to the above range. It should be noted that the stretching time in the stretching belt is not particularly limited, preferably 20 to 40 seconds, more preferably 22 to 30 seconds.
[0115] The width of the film 100 before stretching is preferably 200 to 2000 mm, more preferably 800 to 1200 mm, and the thickness of the film 100 before stretching is preferably 70 to 250 μm, more preferably 100 to 200 μm.
[0116] The film 100 Figure 1 The heating temperature during preheating in the preheating zone shown is preferably 15 to 29° C. higher than the glass transition temperature Tg [° C.] of the acrylic resin constituting the film 100 , and more preferably 19 to 21° C. higher.
[0117] Next, in the manufacturing method of the present invention, the film 100 after stretching is stretched in a stretching belt. Figure 1 The film 100 is transported to a heat relaxation belt, where it is heated to a relaxation temperature T R The film 100 is heated at 1000°C to perform a heat relaxation treatment. As a result, the molecular orientation of the film 100 is made uniform, and the optical characteristics, strength, and durability are improved.
[0118] Relaxation temperature T in the thermal relaxation zone R [°C] is not particularly limited, but is preferably set to Tg [°C] in relation to the glass transition temperature Tg [°C] of the acrylic resin constituting the film 100. R =Tg+10°C to Tg-10°C, more preferably T R =Tg+5℃~Tg-5℃. By making the relaxation temperature T R[°C] is within the above range, so that the values of Zn / Xn and Zn / Yn can be appropriately controlled within the above range. The heat relaxation time in the heat relaxation zone is not particularly limited, but is preferably 5 to 15 seconds, more preferably 9 to 11 seconds.
[0119] As described above, according to the production method of the present invention, it is possible to produce an acrylic resin stretched film in which the values of Zn / Xn and Zn / Yn are controlled within the above ranges.
[0120] The acrylic resin stretched film of the present invention has the values of Zn / Xn and Zn / Yn controlled within the above ranges, and has excellent crack resistance and fracture resistance. Therefore, the acrylic resin stretched film of the present invention can be suitable for various optical applications, such as polarizer protective films, diffusion films, light-collecting films, reflective films, light-guiding films, etc., and can be particularly suitable for use as polarizer protective films. With its excellent crack resistance, it can be particularly suitable for use as polarizer protective films for frameless liquid crystal display devices. Specific embodiments
[0122] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0123] In addition, the evaluation method of each characteristic is as follows.
[0124] <Glass transition temperature Tg of acrylic resin, extrapolated glass transition starting temperature Tig>
[0125] The glass transition temperature Tg (midpoint glass transition temperature) and the extrapolated glass transition start temperature Tig of the acrylic resin were measured using a differential scanning calorimeter (product name "DSC8500", manufactured by PerkinElmer Co., Ltd.) in accordance with the differential scanning calorimetry analysis method based on JIS K7121. In a nitrogen atmosphere, about 10 mg of a sample was kept at 0°C for 1 minute, then the temperature was increased from 0°C to 290°C at a temperature increase rate of 10°C / min, and kept for 3 minutes, then the temperature was decreased to 0°C at a temperature decrease rate of 200°C / min, and kept for 1 minute, and then the temperature was increased from 0°C to 290°C at a temperature increase rate of 10°C / min, and the DSC curve was obtained. Based on the obtained DSC curve, the analysis software attached to the device was used to obtain the result.
[0126] <Polarized Raman Spectroscopy of Stretched Acrylic Resin Film>
[0127] The acrylic resin stretched films obtained in each example and comparative example were analyzed using a laser Raman spectrometer (product name "NRS-5500", manufactured by JASCO Corporation) at a laser wavelength of 532 nm and a measurement range of 600 to 3500 cm -1, grating L600 / 500nm, objective lens 100 times, slit Φ25μm, aperture Φ4000μm, polarizer 0°, exposure time 30 seconds to 150 seconds (at 2930 to 2970cm -1 The peak intensity in the range of 3000 or more was adjusted), and the polarized Raman spectrum was measured under the condition of laser intensity of 3.5 mW to calculate the in-plane anisotropy Yn / Xn and thickness anisotropy Zn / Xn. The measurement and calculation were carried out according to the following steps. It should be noted that the focus of the laser was set to a position 10 μm away from the outermost surface in the depth direction.
[0128] (1) The film winding direction (MD direction) is set as the X direction, the film width direction (TD direction) is set as the Y direction, and the film thickness direction is set as the Z direction. A square measurement sample is accurately cut out with a size of 20 mm in both the X direction and the Y direction. The cut sample is mounted on a sample holder with the axis aligned so that the XY plane can be measured.
[0129] (2) The polarized Raman spectrum in the X direction of the XY plane was measured, and the obtained Raman spectrum was subjected to a second differential process (difference method, data interval 21) using the analysis software provided in the laser Raman spectrometer.
[0130] (3) The peaks at 970 to 1010 cm-1 that depend on the polymer orientation -1 The minimum value of the second differential peak within the range is set as Xd 970-1010 , the peaks at 2930 to 2970 cm-1 that are independent of polymer orientation -1 The minimum value of the second differential peak within the range of 2930-2970 , and then the two peaks are used to perform normalization processing to calculate Xn. It should be noted that Xn = Xd 970-1010 / Xs 2930-2970 .
[0131] (4) Measure the polarized Raman spectrum in the Y direction of the XY plane and calculate Yn in the same way. It should be noted that Yn=Yd 970-1010 / Ys 2930-2970 .
[0132] (5) Calculate the surface anisotropy based on Xn and Yn = Yn / Xn.
[0133] (6) Next, the sample cut out by an ultramicrotome (product name: ULTRACUT UCT, manufactured by Leica Microsystems) is mounted on a sample holder with the axis aligned so that the XZ plane (cut surface) can be measured.
[0134] (7) In the same manner as in the XY plane, the polarized Raman spectrum in the X direction and the polarized Raman spectrum in the Z direction of the XZ plane are measured to calculate Xn and Zn.
[0135] Xn=Xd 970-1010 / Xs 2930-2970
[0136] Zn=Zd 970-1010 / Zs 2930-2970
[0137] (8)Thickness anisotropy = Zn / Xn is calculated from Xn and Zn.
[0138] (9) Based on Yn / Xn and Zn / Xn obtained above, Zn / Yn is calculated.
[0139] Figure 2B , Figure 2C , a curve obtained by polarized Raman spectroscopy measurement of the acrylic resin stretched film of Example 1 is shown. Here, Figure 2A : is a diagram showing the measurement direction of polarized Raman spectroscopy. Figure 2B : is a graph showing a curve obtained by polarized Raman spectroscopy measurement in the X direction of the acrylic resin stretched film of Example 1. Figure 2C 3 is a graph showing a second derivative curve of the polarized Raman spectrum in the X direction of the stretched acrylic resin film of Example 1.
[0140] <Measurement of Thickness of Acrylic Resin Stretched Film>
[0141] The thickness (film thickness) of the acrylic resin stretched film obtained in each of Examples and Comparative Examples was measured using a digital micrometer (manufactured by Mitutoyo Corporation).
[0142] <Measurement of In-Plane Phase Difference R0 and Thickness Direction Phase Difference Rth of Acrylic Resin Stretched Film>
[0143] The in-plane phase difference R0 and the thickness direction phase difference Rth of the acrylic resin stretched film obtained in each embodiment and comparative example at a wavelength of 589nm are calculated as follows: using a phase difference measuring device (product name "KOBRA-WPR", manufactured by Prince Instruments Co., Ltd.) as a measuring device, measuring in low phase mode, and calculating according to the following formula. It should be noted that the thickness direction phase difference Rth is calculated as follows: using an Abbe refractometer (product name "NAR-1T SOLID The average refractive index n of the film measured by ATAGO CO., LTD. ave The three-dimensional refractive index n is obtained by measuring the phase difference Rθ by tilting the slow axis 40° to the tilt axis. x 、n y、n z Then find the value of .
[0144] R0[nm]=(n x -n y )×d
[0145] Rth[nm]={(n x +n y ) / 2-n z}×d
[0146] n x is the refractive index in the slow axis direction where the refractive index in the acrylic resin stretched film plane becomes the largest, n y is the refractive index in the direction perpendicular to the slow axis, n z is the refractive index in the thickness direction of the acrylic resin stretched film, and d is the thickness of the acrylic resin stretched film [nm].
[0147] <Folding test of acrylic resin stretched film (MIT test)>
[0148] The acrylic resin stretched film obtained in each example and comparative example was cut into a size of 100 mm×15 mm and used as a test piece. The MIT folding test number was measured in accordance with JIS P 8115: 2001 using an MIT folding tester (product name: "MIT folding fatigue tester D-2 type", manufactured by Toyo Seiki Seisaku-sho Co., Ltd.) with a load of 1000 gf applied in an atmosphere of a temperature of 23°C and a relative humidity of 50%, with the number of movements set to 175 times / minute and the bending angle set to 135°. The measurement was as follows: samples were taken from three locations in the width direction of the film, and five points were measured for each sample. The average value of the total of nine points (three points × three locations, excluding the maximum value and the minimum value) was taken as the folding number. In the measurement, the result of the test of bending the acrylic resin stretched film perpendicularly to the winding direction (MD direction) is taken as the MIT number in the MD direction, and the result of the test of bending perpendicularly to the direction perpendicular to the winding direction (TD direction) (the result of the test of bending parallel to the winding direction (MD direction)) is taken as the MIT number in the TD direction.
[0149] <Impact Strength of Acrylic Resin Stretched Film>
[0150] The acrylic resin stretched film obtained in each example and comparative example was measured using a film impact tester (manufactured by Toyo Seiki Seisaku-sho, Ltd.). The test piece was formed into a square of 100 mm × 100 mm, and the hammer capacity was set to 1.5 J and the hammer tip diameter was set to 1 inch to perform the test. The test temperature was 23°C, and the impact strength [kJ / m] was recorded as the average value of 10 measurements.
[0151] <Crack resistance test of acrylic resin stretched film>
[0152] The acrylic resin stretched film obtained in each embodiment and comparative example was cut into 300 mm lengths in the MD direction and the TD direction using a super cutter (product name "NZ1-0606", manufactured by Ogino Seiki Seisakusho Co., Ltd.). The cut test piece was observed with a stereo microscope (product name "SMZ1500, manufactured by Nikon Corporation") to find the number of cracks within 50 mm of the cut end. The average value was found from the number of cracks in the MD direction and the TD direction. This was repeated 10 times, and the average value of the 10 measurements was found, and the evaluation was performed based on the following criteria.
[0153] ○: The number of cracks is 3 or less on average.
[0154] △: The number of cracks is less than 6 on average.
[0155] ×: The number of cracks is 7 or more on average
[0156] <Breakage resistance test of acrylic resin stretched film>
[0157] The case where stable production was possible without breakage was marked as 0, and the case where stable production was impossible due to breakage was marked as ×.
[0158] Hereinafter, the present invention will be described in further detail based on Examples, but the present invention is not limited to these.
[0159] [Production Example 1: Production of lactone ring-containing acrylic resin]
[0160] A lactone ring-containing acrylic resin was produced according to the method described in the examples of Japanese Patent No. 4928187. Specifically, 7.95 kg of methyl methacrylate, 1.5 kg of methyl 2-(hydroxymethyl)acrylate, 5.5 kg of styrene, and 10 kg of toluene were placed in a 30 L reaction vessel equipped with a stirring device, a temperature sensor, a condenser, and a nitrogen inlet tube.
[0161] While introducing nitrogen into the reaction vessel, the temperature was raised to 105°C. When reflux was performed, 12 g of tert-amyl peroxyisononanoate was added as a polymerization initiator, and a solution of 24 g of tert-amyl peroxyisononanoate dissolved in 136 g of toluene was added dropwise over 2 hours. Solution polymerization was performed at about 105-110°C under reflux, and further aging was performed over 4 hours. 10 g of a stearyl phosphate / distearyl phosphate mixture (Phoslex A-18, manufactured by Sakai Chemical Industry Co., Ltd.) was added to the obtained acrylic copolymer solution, and a cyclocondensation reaction was performed at about 120°C under pressure for 5 hours. 10 g of octyl phosphate (Phoslex A-8, manufactured by Sakai Chemical Industry Co., Ltd.) was added to the obtained acrylic copolymer solution, and a cyclocondensation reaction was performed at about 120°C under pressure for 5 hours. Next, a ventilated twin-screw extruder ( The obtained acrylic copolymer solution was introduced into a toluene-based reactor at a treatment rate of 2.0 kg / h in terms of the amount of resin, and a devolatilization treatment was performed at a barrel temperature of 240° C., a rotation speed of 120 rpm, and a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg), and a polymer filter treatment was performed. During the above treatment, zinc octoate (Nikka Octhix Zinc, manufactured by Nippon Chemical Industry Co., Ltd.) as a foaming inhibitor was injected between the second front vent and the third front vent so as to be 1400 ppm relative to the acrylic copolymer obtained in the form of a toluene solution.
[0162] A water tank filled with filtered clean cooling water was arranged at the front end of the twin-screw extruder, and the strands were cooled and introduced into a pelletizer, thereby obtaining transparent pellets of a heat-resistant acrylic resin having a structural unit having a lactone ring and a structural unit derived from an aromatic monomer. The glass transition temperature Tg and the extrapolated glass transition starting temperature Tig of the obtained resin were measured according to the above method, and the glass transition temperature Tg was 125°C and the extrapolated glass transition starting temperature Tig was 123°C.
[0163] [Production Example 2: Production of Glutarimide Ring-Containing Acrylic Resin]
[0164] According to the method described in the embodiment of Japanese Patent No. 5574787, an acrylic resin containing a lactone ring is manufactured. That is, a tandem type reaction extruder connected in series with two extrusion reactors is used to manufacture resin. About the tandem type reaction extruder, the first extruder (1) and the second extruder (2) all use a co-directional meshing twin-screw extruder with a diameter of 75 mm and a L / D (ratio of the length L of the extruder to the diameter D) of 74, and a constant weight feeder (KUBOTA Corporation system) is used to supply raw material resin to the first extruder raw material supply port. In addition, the decompression degree of each exhaust port in the first extruder and the second extruder is set to -0.095 MPa. Furthermore, a pipe with a diameter of 38 mm and a length of 2 m is used to connect the first extruder and the second extruder, and a constant flow pressure valve is used as the component internal pressure control mechanism connecting the resin discharge port of the first extruder and the raw material supply port of the second extruder. The resin (strand) discharged from the second extruder is cooled on a cooling conveyor and then cut into pellets using a pelletizer. Here, in order to adjust the pressure in the component connecting the resin discharge port of the first extruder and the raw material supply port of the second extruder or estimate extrusion fluctuations, a resin pressure gauge is provided at the first extruder outlet, the central part of the component connecting the first extruder and the second extruder, and the second extruder outlet.
[0165] Regarding the first extruder, polymethyl methacrylate resin (Mw: 105,000) was used as the raw material resin, and monomethylamine was used as the imidizing agent to produce the imide resin intermediate 1. At this time, the temperature of the highest temperature section of the extruder was set to 280°C, the screw speed was set to 55 rpm, the raw material resin supply was set to 150 kg / hour, and the amount of monomethylamine added was set to 2.0 parts relative to 100 parts of the raw material resin. In addition, a constant flow pressure valve was set just before the raw material supply port of the second extruder, and the first extruder was adjusted in such a way that the pressure of the monomethylamine injection section became 8 MPa.
[0166] Regarding the second extruder, after the imidization reaction reagent and by-products remaining at the rear vent and the vacuum exhaust port are devolatilized, a mixed solution of dimethyl carbonate and triethylamine as an esterifying agent is added to produce an imide resin intermediate 2. At this time, the temperature of each barrel of the extruder is set to 260°C, the screw speed is set to 55 rpm, the amount of dimethyl carbonate added is set to 3.2 parts relative to 100 parts of the raw resin, and the amount of triethylamine added is set to 0.8 parts relative to 100 parts of the raw resin. Furthermore, after removing the esterifying agent in the exhaust port, it is extruded from a strand die, cooled in a water tank, and pelletized in a pelletizer, thereby obtaining a resin composition.
[0167] (Production of optical thin films)
[0168] <Example 1>
[0169] The resin pellets obtained in Preparation Example 1 were melt-extruded at a temperature of 265°C to form an unstretched film having a width of 1000 mm and a thickness of 180 μm. The two ends of the film were then clamped with a clamp and supplied to a Figure 1 The film was heated to 145°C in the preheating zone, and then heated to 150°C in the stretching zone, and stretched at 2.0 times in the longitudinal direction and 2.2 times in the transverse direction, with a longitudinal strain rate of 150% / min and a transverse strain rate of 150% / min. After stretching, the film was relaxed at 125°C in the heat relaxation zone to obtain a stretched film with an average film thickness of 40 m.
[0170] <Example 2>
[0171] A stretched film was obtained in the same manner as in Example 1 except that the temperature of the stretching belt was set to 151°C.
[0172] <Example 3>
[0173] A stretched film was obtained in the same manner as in Example 1 except that the temperature of the stretching belt was set to 153°C.
[0174] <Example 4>
[0175] A stretched film was obtained in the same manner as in Example 1 except that the temperature of the stretching belt was set to 154°C.
[0176] <Example 5>
[0177] The resin pellets obtained in Preparation Example 1 were melt-extruded at a temperature of 265° C. to form an unstretched film having a width of 300 mm and a thickness of 130 μm, thereby obtaining an unstretched film having an average film thickness of 130 μm. Next, a square unstretched film sample having a winding direction (X direction) and a width direction (Y direction) of 95 mm was accurately cut out from the obtained unstretched film.
[0178] The unstretched film sample cut out was subjected to simultaneous biaxial stretching using a biaxial stretching apparatus (product name "X6H-S", manufactured by Toyo Seiki Seisaku-sho Co., Ltd.) to obtain a stretched film having an average film thickness of 35 μm. It should be noted that the stretching was performed as follows: the stretching temperature was 150° C., the stretching ratio in the X direction was 2.0 times, the stretching speed in the X direction was 200% / min, the stretching ratio in the Y direction was 2.0 times, and the stretching speed in the Y direction was 200% / min.
[0179] <Example 6>
[0180] The same procedure as in Example 5 was carried out except that the stretching temperature was 151°C.
[0181] <Comparative Examples 1 to 7>
[0182] A stretched film was obtained in the same manner as in Example 1 except that the temperatures of the stretching belt were set at 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, and 149°C, respectively.
[0183] <Comparative Example 8>
[0184] The same procedure as in Example 1 was carried out except that the temperature of the stretching belt was set to 155° C. A stretched film could not be obtained due to breakage.
[0185] <Comparative Example 9>
[0186] An unstretched film of 180 μm that was not stretched was used.
[0187] <Comparative Example 10>
[0188] The resin pellets obtained in Preparation Example 2 were melt-extruded at a temperature of 265° C. to form an unstretched film having a width of 1000 mm and a thickness of 180 μm. The two ends of the film were then clamped with a clamp and supplied to a Figure 1 The film was heated to 150°C in a preheating zone, and then heated to 145°C in a stretching zone, and stretched at 2.0 times in the longitudinal direction and 2.2 times in the transverse direction, with a longitudinal strain rate of 150% / min and a transverse strain rate of 150% / min. After stretching, the film was relaxed at 125°C in a heat relaxation zone to obtain a stretched film with an average film thickness of 40 m.
[0189] <Comparative Example 11>
[0190] The resin pellets obtained in Preparation Example 1 were melt-extruded at a temperature of 265° C. to form an unstretched film having a width of 300 mm and a thickness of 130 μm, thereby obtaining an unstretched film having an average film thickness of 130 μm. Next, a square unstretched film sample having a winding direction (X direction) and a width direction (Y direction) of 95 mm was accurately cut out from the obtained unstretched film.
[0191] The cut unstretched film sample was sequentially biaxially stretched using a biaxial stretching device (product name "X6H-S", manufactured by Toyo Seiki Seisaku-sho Co., Ltd.) to obtain a stretched film with an average film thickness of 20 μm. It should be noted that the first stage of stretching was carried out along the X direction, at a stretching temperature of 150° C., a stretching ratio of 3.0 times, and a stretching speed of 1000% / min, and the second stage of stretching was carried out along the Y direction, at a stretching temperature of 150° C., a stretching ratio of 3.0 times, and a stretching speed of 1000% / min.
[0192] <Comparative Example 12>
[0193] The same procedure as in Example 5 was carried out except that the strain rate was set to 1000% / min.
[0194] <Comparative Example 13>
[0195] The same procedure as in Comparative Example 12 was carried out except that the stretching temperature was 151°C.
[0196] <Reference example>
[0197] The resin pellets obtained in Manufacturing Example 1 were melt-extruded at a temperature of 265° C. to form an unstretched film having a width of 300 mm and a thickness of 130 μm, thereby obtaining an unstretched film having an average film thickness of 130 μm. Next, a rectangular unstretched film sample having a length of 90 mm in the winding direction (X direction) and a length of 150 mm in the width direction (Y direction) was accurately cut out from the obtained unstretched film.
[0198] The unstretched film sample cut out was subjected to free-end uniaxial stretching in the X direction using a TENSILON universal material testing machine (product name "RTA-500", manufactured by Orientec Corporation) with the chuck spacing set to 50 mm, to obtain a stretched film having an average film thickness of 46 μm. It should be noted that the stretching was carried out in the X direction at a stretching temperature of 130° C., a stretching ratio of 2.8 times, and a stretching speed of 1000% / min.
[0199] Then, the above-mentioned measurements were performed using the obtained acrylic resin stretched film. The results are shown in Table 1.
[0200] [Table 1]
[0201]
[0202] Table 1 also shows the results of the in-plane orientation degree Dpl and the thickness orientation degree Dth in polarized Raman spectroscopy, which were measured by the method disclosed in Japanese Patent Application Laid-Open No. 2010-58455.
[0203] As shown in Table 1, acrylic resin was used and the stretching temperature T E [°C] is expressed as T in relation to the glass transition temperature Tg [°C] of the acrylic resin. E =Tg+25~Tg+29, the longitudinal tensile strain rate (tensile strain rate in the MD direction) is 90~600% / min, and the transverse tensile strain rate (tensile strain rate in the TD direction) is 90~600% / min, the Zn / Xn and Zn / Yn of the obtained acrylic resin stretched film obtained by polarization Raman spectroscopy can appropriately satisfy the following formula (1) and the following formula (2), thereby achieving excellent crack resistance and fracture resistance (Examples 1 to 6).
[0204] Zn / Xn≤1.00···(1)
[0205] Zn / Yn ≤ 1.00 ··· (2)
[0206] On the other hand, when the stretching temperature T E [°C] in relation to the glass transition temperature Tg [°C] of the acrylic resin is such that T E < Tg + 25, Zn / Xn and Zn / Yn obtained by polarized Raman spectroscopy of the obtained stretched acrylic resin film no longer satisfy either of the above formulas (1) and (2), and the crack resistance is poor (Comparative Examples 1 to 7, Comparative Example 10).
[0207] On the other hand, when the stretching temperature T E [°C] in relation to the glass transition temperature Tg [°C] of the acrylic resin is such that T E > Tg + 29, the fracture resistance is poor (Comparative Example 8).
[0208] In addition, in the case of an unstretched film, it is wound up in the winding direction during film formation. Therefore, Zn / Xn and Zn / Yn obtained by polarized Raman spectroscopy also no longer satisfy either of the above formulas (1) and (2), and the orientation state is different from that of the film of the present invention (Comparative Example 9).
[0209] In the case of a testing machine rather than a production machine, when the stretching temperature, the longitudinal stretching strain rate, and the transverse stretching strain rate exceed the appropriate ranges, Zn / Xn and Zn / Yn obtained by polarized Raman spectroscopy also no longer satisfy either of the above formulas (1) and (2), and the crack resistance is poor (Examples 5 to 6, Comparative Examples 11 to 13).
Claims
1. An acrylic resin stretched film, which is an acrylic resin stretched film formed by molding an acrylic resin, wherein Zn / Xn and Zn / Yn of the acrylic resin stretched film obtained by polarization Raman spectroscopy satisfy the following formula (1) and the following formula (2), Zn / Xn≤1.00···(1) Zn / Yn≤1.00···(2) Xn is given by Xn=Xd 970-1010 / Xs 2930-2970 The calculated value, Yn is given by Yn=Yd 970-1010 / Ys 2930-2970 The calculated value, Zn is Zn=Zd 970-1010 / Zs 2930-2970 The calculated value, XD 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarization Raman spectroscopy measurement parallel to the winding direction (MD direction) of the acrylic resin stretched film (X direction). -1 The minimum value of the second differential peak of the peak within the range of Xs 2930-2970 The wave number is 2930 to 2970 cm-1 obtained by polarization Raman spectroscopy measurement parallel to the winding direction (MD direction) of the acrylic resin stretched film (X direction). -1 The minimum value of the second differential peak of the peak within the range of Y 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy measurement perpendicular to the winding direction (MD direction) of the acrylic resin stretched film (Y direction). -1 The minimum value of the second differential peak of the peak within the range of Ys 2930-2970 The wave number is 2930 to 2970 cm-1 obtained by polarized Raman spectroscopy measurement perpendicular to the winding direction (MD direction) of the acrylic resin stretched film (Y direction). -1 The minimum value of the second differential peak of the peak within the range of Zd 970-1010 The wave number is 970 to 1010 cm-1 obtained by polarized Raman spectroscopy along the thickness direction (Z direction) of the acrylic resin stretched film. -1 The minimum value of the second differential peak of the peak within the range of Z 2930-2970 The wave number is 2930-2970cm obtained by polarized Raman spectroscopy along the thickness direction (Z direction) of the acrylic resin stretched film. -1 The minimum value of the second differential peak of the peak within the range. 2 . The stretched acrylic resin film according to claim 1 , wherein the in-plane retardation R0 of the stretched acrylic resin film with respect to light having a wavelength of 589 nm is 10 nm or less. 3 . The stretched acrylic resin film according to claim 1 , wherein the thickness direction phase difference Rth with respect to light of a wavelength of 589 nm is -10 to +10 nm. 4 . The acrylic resin stretched film according to claim 1 , which has a glass transition temperature (Tg) of 100° C. to 200° C.
5. The acrylic resin stretched film according to claim 1, wherein The acrylic resin contains a (meth)acrylic polymer having a ring structure.
6. The acrylic resin stretched film according to claim 5, wherein The acrylic resin includes a (meth)acrylic polymer having a ring structure in the main chain.
7. The acrylic resin stretched film according to claim 5, wherein The ring structure is at least one selected from the group consisting of a lactone ring structure, a glutarimide structure, a glutaric anhydride structure, an N-substituted maleimide structure, and a maleic anhydride structure.
8. The acrylic resin stretched film according to claim 5, wherein The ring structure is a lactone ring structure.
9. The acrylic resin stretched film according to claim 1, wherein The acrylic resin contains a UV absorber.
10. The acrylic resin stretched film according to claim 1, which has a film thickness of 35 to 45 μm. 11 . A polarizer protective film comprising the stretched acrylic resin film according to claim 1 .
12. A method for producing a stretched acrylic resin film, the method comprising a stretching step of stretching a film of an acrylic resin, The stretching temperature in the stretching step is glass transition point Tg+25°C to 29°C, and the stretching strain rate is 90 to 600% / min.
Citation Information
Patent Citations
JP1974028187A
Air conditioner for automatic malting device
JP1980074787A
Production and use of clear heat-resistant resin
JP2000230016A
Method of manufacturing for transparent heat resistant resin and use of the same
JP2001151814A
Transparent thermoplastic resin laminate
JP2002120326A